181 UNDERSTANDING OLDER ADULTS' PERCEPTIONS AND EXPERIENCES OF NOVELTY: A PILOT STUDY. (25th October 2022) - Tsabary, C; Hopper, L; Kilcullen, S; Gallagher, P
Abstract: Background: Our institution is currently developing a technology solution to support adults to live well at home for longer. As the system develops, there is an emerging emphasis on strict structure/routine in older adults' activities of daily living. In contrast, engagement in novel experiences is widely endorsed as a buffer against cognitive decline. Despite this, there is scant research into the perceptions and experiences of novelty in older adults. Understanding older adults' views on novelty is necessary to inform the advancement of the current project. Methods: A multiple-methods, exploratory approach was used. A 90-minute focus group was held with 4 older adults to explore their conceptualisations of novelty, discussing what constitutes a novel experience and gauging the value placed on routine and novelty in daily life. Questionnaires measuring Mental Well-Being (MWB), personality, Novelty-Need Satisfaction (NNS), and preference for routine were subsequently completed by each participant. Results: Four main themes emerged from the qualitative data. They comprised the contrast between planned and unplanned novel experiences, the influence of context on the enjoyment of novelty, the value of the vicarious experience of novelty and the challenge associated with change at a social/global level. The quantitative data revealed that 91.9% of the variation in MWB is attributed to its relationship with NNS. Conclusion: The focus group served as a strong foundation; especially into the contextual influence of both internal (psychological/attitude-related) and external (environmental/social) factors upon the enjoyment of novelty; as well as indicating that further research is merited into the contrasting views on planned and unplanned novel experiences. The quantitative data corroborate the importance of maintaining novelty in older age. Understanding how to preserve novelty while supporting routines will allow assistive technology projects such as this, to adopt a holistic approach and encourage consideration for this aspect of life, often neglected in the lives of older adults.